(untitled) (European journal of volunteering and community-based projects, 2021)
Offering HIV testing at a social event attended mainly by young men who have sex with men (MSM) provides a unique opportunity to intervene in the early HIV diagnosis process. The Turin Fast Track City project makes it possible to observe organizational elements useful for the organization of rapid tests on the territory, at the same time joining the COBATEST Network provides the possibility of observing a sample by determining the variables useful for the construction of intervention strategies and prevention campaigns. The administration of HIV rapid tests by associations is a key tool for increasing the number of subjects who undergo the test, access treatment early and are informed about treatments and possible risk behaviors.